Orthodontic treatment needs in children and its relationship with gender, family income and ethnic groups - Valdeci Elias dos Santos Junior; Priscila Lima de Luna Freire; Arnoldo Vasconcelos de Alencar Filho; Mônica Vilela Heimer; Aronita Rosenblatt (Editorial Ciencias Médicas, 2015)
Background: Malocclusions are considered public health problems, needing an uniform method of assessment that prioritizes the attendance of individuals with greater orthodontic treatment need, with this purpose, the Index of Orthodontic Treatment Need has been used in many countries. Aim: The study aimed to evaluate the orthodontic treatment need in school going children, attending in Recife, northeast Brazil and also establishes its relationship with gender, family income and ethnic groups. Methods: 433 children, aged 6-12 years formed the sample. The dental health component grades it was recorded to define the orthodontic treatment need. Results: The findings revealed that 63% of children had at least one type of malocclusion; 40.5% had no need for orthodontic treatment (Grade 1 and 2); 5.5% were borderlines, indicating moderate need (Grade 3); 54% had definite treatment (Grade 4), but no children were classified in grade 5. No statistically significant differences were found between genders (p=0.217), family income (p=0.176) and ethnic groups (p=0.281). Conclusion: The most of the children had moderate and great orthodontic needs treatment. There was no association between orthodontic treatment need and gender, family income or ethnic groups.